2012
DOI: 10.1371/journal.pone.0048810
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus-6A/B Binds to Spermatozoa Acrosome and Is the Most Prevalent Herpesvirus in Semen from Sperm Donors

Abstract: An analysis of all known human herpesviruses has not previously been reported on sperm from normal donors. Using an array-based detection method, we determined the cross-sectional frequency of human herpesviruses in semen from 198 Danish sperm donors. Fifty-five of the donors had at least one ejaculate that was positive for one or more human herpesvirus. Of these 27.3% (n = 15) had a double herpesvirus infection. If corrected for the presence of multiple ejaculates from some donors, the adjusted frequency of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 21 publications
(21 reference statements)
0
30
0
3
Order By: Relevance
“…Other cell types such as monocytes, dendritic cells, astrocytes, and glial cells are permissive for infection. HHV6A and HHV-6B can bind to the sperm acrosome, providing a possible route to germline integration [19]. The ability of HHV-6A and HHV-6B to infect olfactory-ensheathing glial cells that are present in the nasal cavity may provide a route to the central nervous system [20].…”
Section: Productive Replicationmentioning
confidence: 99%
“…Other cell types such as monocytes, dendritic cells, astrocytes, and glial cells are permissive for infection. HHV6A and HHV-6B can bind to the sperm acrosome, providing a possible route to germline integration [19]. The ability of HHV-6A and HHV-6B to infect olfactory-ensheathing glial cells that are present in the nasal cavity may provide a route to the central nervous system [20].…”
Section: Productive Replicationmentioning
confidence: 99%
“…Indeed, Csoma et al [112] detected KI virus and WU virus in the urine of renal transplants but not in the control groups. Moreover, immunosuppression due to pregnancy led to a higher prevalence of BK virus in urine samples in pregnant women compared to non-pregnant women [113]. …”
Section: Exploring the Viral Flora In Humansmentioning
confidence: 99%
“…In this case it appears that some herpesviruses, such as human Herpesvirus 6 A/B or the Cytomegalovirus, were able to attach to the sperm head with an intact acrosome [108,113]. Thus, given the potential risk some herpesviruses may represent to the newborns, additional research is required to evaluate the impact of this asymptomatic shedding from herpesvirus-positive donor semen.…”
Section: Exploring the Viral Flora In Humansmentioning
confidence: 99%
“…Except for one study from Greece [23], there is agreement that VZV is neither present in semen from fertility-clinic attendants (Germany) [11], nor from men of couples undergoing IVF treatment (Spain) [22], or from healthy sperm donors (Denmark) [18]. Taken together, the evidence indicates that VZV is not present in semen, perhaps reflecting the infrequency of VZV reactivation occurring from the ganglia rather than immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al found HHV-6A/B in 2.0% of infertility patients from China [14], whereas Michou et al detected HHV-6A/B in 8.2% of 109 men from couples undergoing IVF treatment in Spain [22]. A slightly higher prevalence of 13.5% was seen by Kaspersen et al in semen from Danish sperm donors [18] (Table 2), suggesting that the prevalence of HHV-6A/B is not increased among patients attending a fertility clinic. A remarkably high prevalence of 66.8% among men attending a fertility clinic on Crete has been reported by Neofytou et al using nested PCR [23].…”
Section: Introductionmentioning
confidence: 99%